Juridical review in civil law on acts of default (wanprestasi) in land sale and purchase agreement cases (case study: Decision number 840/Pdt.G/2023/PN Mdn) - Situmorang, Frandika; Marbun, Jonatan; Purba, Bonaraja (Journal of Law Science, 2025)
This research was conducted to provide a juridical analysis concerning acts of breach of contract occurring in a land sale and purchase agreement based on the Case Study of Decision Number 840/Pdt.G/2023/PN Mdn. The legal issues addressed in this research include the definition, elements, and legal consequences of unlawful acts and breach of contract in the context of land sale and purchase agreements. The research method used is a normative juridical approach by analyzing court decisions as the primary data source. The results of the study indicate that in the case under review, both unlawful acts and breach of contract may lead to the cancellation of the agreement and the obligation to provide compensation. The conclusion of this research emphasizes the importance of legal protection for parties involved in land sale and purchase agreements, aiming to ensure that rights and obligations are realized in accordance with the applicable laws and regulations.